The frequency of mitral valve prolapse in electrocardiographic disturbances of unknown origin - Saraçlar, Muhsin; Özme, Şencan; Özkutlu, Süheyla; Usanmaz, İsmet (The Turkish Journal of Pediatrics, 1981)
With the wide application of echocardiography, mitral valve prolapse syndrome has been detected easily and frequently. Available data indicate that mitral valve prolapse is common in the general population. Since all age groups of patients with mitral valve prolapse are susceptible to bacterial endocarditis, it is important to identify the presence of this condition as early as possible. To our knowledge, the frequency of mitral valve prolapse in patients with ECG abnormalities of unknown origin has not been determined. This study is aimed at answering this question. Sixty-six cases, including 40 patients with ECG disturbances of unknown etiology and 26 controls, were studied echocardiographically. Of the 40 patients, 24 had mitral valve prolapse (60%). In order to apply prophylactic measures for bacterial endocarditis, mitral valve prolapse should be sought in all cases having ECG changes of unknown origin.